Under nutrition and associated factors among adolescent girls in Fik district, Erar zone, Somali region, Ethiopia, 2019 - Ali, Abdisalan Muktar; Abdi, Abdirahman Abdisamed (International Journal Of Community Medicine And Public Health, 2022)
Background: Malnutrition in adolescent is a major public health problem in the world, especially in developing countries, which is responsible for bone mass disability and affects their ability to learn and work at maximum productivity. Despite this, there is a shortage of information on the nutritional status of adolescent girls in Somali region, Ethiopia. This study was therefore performed to help redress this lack of data and to provide information for future improvements by health planners and policy makers. Method: Data were collected from 538 adolescent girls aged 10-19 years by community cross sectional study design. WHO Anthro-plus software was used to analyze nutritional statuses of adolescent girls and magnitudes were determined using WHO 2007 references point. Data were entered into Epi data and transferred to SPSS (version 20) for analysis. Multivariable logistic regression was used to measure the association between the dependent variable and independent variables with 95% confidence interval Results: The result of the study revealed that prevalence of thinness and stunting are 32.7% and 2.8% respectively. Factors independently associated with thinness were age of adolescent girl (AOR=0.50, 95% CI=0.27-0.92), mother education status (AOR=2.30, 95% CI=0.72-7.36), father occupation (AOR=0.44, 95% CI0.22-0.87), dietary diversity score (AOR= 0.61, 95% CI=0.38-0.97) and less than two daily meal frequencies (AOR= 2.17, 95% CI=1.00-4.69). Conclusions: The prevalence of thinness was high in the study area. Thus, focus should be given adolescent girls nutrition and provide a unique opportunity to break the intergenerational cycle of malnutrition. The government, school teacher and parents should give more attention to adolescent girls as they are crucial segment of the population and develop strategies on improvement of dietary diversity intake.